NATIONAL PRODUCTIVITY OF THE SOUTHEAST ASIAN COUNTRIES - Kao, Chiang (European Scientific Journal, ESJ, 2014)
Since the financial crisis of 1997, Southeast Asia’s fast recovery and continued development has surprised the world. This paper investigates national productivity of the ten Southeast Asian countries. The high national productivity explains why the economy of this region developed steadily after the financial crisis. From the viewpoint of labor productivity and capital productivity, the ten countries are classified as high-productivity, lowproductivity, labor-intensive, and capital-intensive countries. Together with another indicator used by many economists to represent living standards, GDP per capita, the Southeast Asian countries are categorized into four types: fast growing-moderate living standards, fast growing-low living standards, stable growing-high living standards, and slow growing-low living standards. Categorization into corresponding groups facilitates subsequent inference regarding their characteristics and stage of economic development. More importantly, weak areas are identified for future improvement.